VO2max Intensity Through Interval Training and Circuit Training - Firmansyah Dahlan; Alimuddin Alimuddin (JUARA : Jurnal Olahraga, 2019)
Research Objectives To determine the effect and differences in the effect of interval training and circuit training. To find out the interaction between Interval Training and Circuit Training*Gender on Cardovascular Endurance (Vo2max) Penjas Teachers in Palopo City with a middle age range between the ages of 45 to 59 years. The type of research used is the type of experiment. The design of this study uses 2x2 factorial design. Dependent Variables (Interval Training and Circuit Training). The population is 426 teachers, 20 of which are selected using a purposive sampling technique. The test instrument used is Aerobic Test. The results showed that the Interval Training and Circuit Training had an influence on increasing Cardovascular Endurance (Vo2max), there were differences in the effect of the Interval Training and Circuit Training exercises but at an insignificant level, there was no interaction between Interval Training and Circuit Training*Gender to Power Cardovascular Resistant (Vo2max) Penjas teachers in the city of Palopo are middle ages between the ages of 45 and 59 years.